Enhanced selectivity and activity for electrocatalytic reduction of CO2 to CO on an anodized Zn/carbon/Ag electrode. Issue 28 (5th July 2019) - Gao, Yugang; Li, Fengping; Zhou, Peng; Wang, Zeyan; Zheng, Zhaoke; Wang, Peng; Liu, Yuanyuan; Dai, Ying; Whangbo, Myung-Hwan; Huang, Baibiao
Abstract : The selectivity and activity of the anodized Zn/C/Ag composite electrode containing a tiny amount of Ag (∼0.5 wt%) are enhanced by the synergistic effect of Zn, C and Ag. Abstract : We constructed a composite electrode by depositing a C/Ag mixture containing a tiny amount of 20 nm Ag NPs (∼0.5 wt%) on anodized Zn (AZ) metal. The AZ/C/Ag electrode exhibits greatly enhanced CO selectivity (∼86%) and activity (∼7.3 mA cm −2 ) on comparison with the GCE/C/Ag electrode (∼24% and ∼2.3 mA cm −2 ). The experimental results show that the enhanced CO2 reduction performance of the AZ/C/Ag electrode is attributed to the synergistic effect of AZ, C and Ag. Density functional theory calculations indicate that the enhanced CO selectivity may originate from the enhanced stabilization of CO2 and COOH* on the AZ/C/Ag electrode surface. This electrode also shows great mass activity and stability for CO2 reduction. Our work provides a new and simple way to fabricate efficient catalysts with high selectivity, activity and stability for electrocatalytic CO2 reduction.